Faktor-Faktor Yang Mempengaruhi Perataan Laba - Surya, Monita Permata; Ponziani, Regi Muzio (Media Bisnis, 2025)
This research aims to determine the effect of firm size, firm value, profitability, leverage, dividend policy, and public ownership on income smoothing. The population of this research is manufacturing companies listed on the Indonesia Stock Exchange (IDX). The method used for sample selection is the purposive sampling method. With this method obtained 102 companies that meet the criteria that have been set as research samples. This research uses logistic regression for data analysis. The result of the research is dividend policy influences with a positive correlation on income smoothing. Having a positive correlation means that the higher the dividend payout ratio, the greater motivation to perform income smoothing. While firm size, firm value, profitability, leverage, and public ownership did not influence on income smoothing.